A Novel Method for Non-invasive Estimation of Primary Productivity in Aquatic Ecosystems Using a Chlorophyll Fluorescence-Induced Dynamic Curve - Chen, Hui; Li, Kunfeng; Xue, Chunling; Wang, Qiang (Frontiers in Microbiology, 2021)
Photosynthetic microalgae are a major contributor to primary productivity in aquatic ecosystems, but typical measurements of their biomass and productivity are costly and relatively inefficient. The chlorophyll fluorescence induced dynamic (OJIP) curve can reflect the original photochemical reaction and the changes to the function and structure of photosystems, as well as the effects of environmental factors on photosynthetic systems. Here, we present a novel method for estimating the Chl a content and photosynthetic microalgal cell density in water samples using the integral area of OJIP curve. We identified strong linear relationships between OJIP curve integrals and both Chl a contents and cell densities for a variety of microalgal cultures and natural communities. Based on these findings, we present a noninvasive method to estimate primary productivity in aquatic ecosystems and monitor microalgal populations. We believe that this technique will allow for widespread, rapid, and inexpensive estimating water primary productivity and monitoring of microalgal populations in natural water. This method is potentially useful in health assessment of natural water and as an early warning indicator for algal blooms.